Reliability of a telephone interview for the classification of headache disorders - Angermaier, Anselm; Koennecke, Andy; Kloetzer, Christine; Strauss, Sebastian; Fleischmann, Robert (Frontiers in Neurology, 2023)
Objective: Test the reliability of a semi-structured telephone interview for the classification of headache disorders according to the ICHD-3.Background: Questionnaire-based screening tools are often optimized for single primary headache diagnoses (e.g. migraine (MIG), tension headache (TTH)) and therefore insufficiently represent the diagnostic precision of the ICHD-3, which limits epidemiological research of rare headache disorders. Brief semi-structured telephone interviews could be an effective alternative to improve classification.A patient population representative of different primary and secondary headache disorders (n=60) was recruited from the outpatient clinic (HSA) of a tertiary care headache center. These patients completed an established population-based questionnaire for the classification of MIG, TTH or trigeminal autonomic cephalgia (TAC). In addition, they received a semi-structured telephone interview from three blinded headache specialists, individually. Agreement of diagnoses made either using the questionnaires or interviews with the HSA diagnoses was evaluated.Results: Of the 59 patients (n=1 dropout), 24% had a second-order and 5% a third-order headache disorder. Main diagnoses were as follows: frequent primary headaches 61% MIG, 10% TAC, 9% TTH, 5% rare primary and 16% secondary headaches. Second-order diagnoses were chronic migraine throughout, third-order diagnoses were medication overuse headache and TTH. Agreement between main headaches from the HSA was significantly better for the telephone interview than for the questionnaire (questionnaire: κ=0.330; interview: κ=0.822;p<0.001). Second-order diagnoses were not adequately captured by questionnaires, while there was a trend for good agreement with the telephone interview (κ=0.433; p=0.074).Headache frequency and psychiatric comorbidities were independent predictors of HSA and telephone interview agreement. Male gender, headache frequency, severity and depressive